PBMC transcriptome changes in beef steers with negative or positive residual feed intake following in vitro LPS stimulation - Leal, Yarahy; Johnson, Samanthia; Idowu, Modoluwamu; Taiwo, Godstime; Sidney, Taylor; Treon, Emily; Ologunagba, Deborah; Gratz, Luke M.; Morenikeji, Olanrewaju B.; Ogunade, Ibukun M. (Frontiers in Animal Science, 2025)
We investigated the changes in the PBMC transcriptome profile of beef steers with divergent residual feed intake (RFI) following in vitro LPS stimulation. Negative-RFI beef steers (n =8, RFI= -2.00) and positive-RFI beef steers (n = 8, RFI = +1.59) were identified from a group of 40 crossbred beef steers (average BW = 360 ± 7.3 kg) after a 56-d RFI testing period. Whole blood samples were collected for PBMC extraction and were stimulated for 2 hours with LPS, followed by total RNA extraction and sequencing. The gene expression profiles of LPS-stimulated PBMCs and the LPS-unstimulated control group from negative- or positive- RFI beef steers were compared and analyzed. Differentially expressed genes were determined using FDR ≤ 0.05. In negative-RFI beef steers, there were 37 differentially expressed genes; the expression of 28 genes such as CD14, TREM1, THBS1, S100A12, S100A8, S100A9, CXCL5, IL1RN, and CCL20 were downregulated, whereas expression of 9 genes including CCL22, CD83, TRAF1, NFKBIZ, RSG16, CD60, and IL17A were upregulated in LPS-stimulated PBMC. In positive-RFI beef steers, we found 9 differentially expressed genes (CCL22, CD83, NFKBIZ, E1BK63, TRAF1, BCL2A1, IFNLR1, RSG16, and CD40), all of which were all upregulated. Gene ontology analysis of the differentially expressed genes revealed the enrichment of biological pathways related to defense and innate immune response, cell migration, and cellular response to lipopolysaccharide in negative-RFI beef steers, characteristic of a prompt and efficient immune reaction. In positive-RFI beef steers, biological processes associated with T cell activation and differentiation, positive regulation of adaptive immune response, and immune cell surface receptors were differentially enriched. Taken together, these findings suggest that negative-RFI beef steers may possess a more competent and energy-conserving immune response, marked by a quicker resolution of inflammation and a balanced pro- and anti-inflammatory response. These results enhance the understanding of the molecular mechanisms underlying feed efficiency, highlighting the potential role of immunocompetence in improving livestock productivity.